Complete Extension and Join of Two Graphs - B, Athul T; John, Roy; N, Manju V; K, Akhil C. (International Journal of Basic and Applied Sciences, 2025)
In 2016 [5], Suresh Singh G and Sunitha Grace Zacharia introduced the concept of graph extension by adding edges to G in a particular way. In this paper, we try to find out some classes of graphs whose joint is completely extendable.